Arab spring : negotiating in the shadow of the intifadat - Zartman, I. William (Studies in security and international affairs., 2015)
Beginning in January 2011, the Arab world exploded in a vibrant demand for dignity, liberty, and achievable purpose in life, rising up against an image and tradition of arrogant, corrupt, unresponsive authoritarian rule. These previously unpublished, countryspecific case studies of the uprisings and their still unfolding political aftermaths identify patterns and courses of negotiation and explain why and how they occur. The contributors argue that in uprisings like the Arab Spring negotiation is "not just a 'nice' practice or a diplomatic exercise." Rather, it is a "dynamically multilevel" process involving individuals, groups, and states with continually shifting priorities-and with the prospect of violence always near. From that perspective, the essaysits analyze a range of issues and events-including civil disobedience and strikes, mass demonstrations and nonviolent protest, and peaceful negotiation and armed rebellion-and contextualize their findings within previous struggles, both within and outside the Middle East. The Arab countries discussed include Algeria, Bahrain, Egypt, Libya, Morocco, Syria, Tunisia, and Yemen. The Arab Spring uprisings are discussed in the context of rebellions in countries like South Africa and Serbia, while the Libyan uprising is also viewed in terms of the negotiations it provoked within NATO. Collectively, the essays analyze the challenges of uprisers and emerging governments in building a new state on the ruins of a liberated state; the negotiations that lead either to sustainable democracy or sectarian violence; and coalition building between former political and military adversaries. Contributors: Samir Aita (Monde Diplomatique), Alice Alunni (Durham University), Marc Anstey* (Nelson Mandela University), Abdelwahab ben Hafaiedh (MERC), Maarten Danckaert (European-Bahraini Organization for Human Rights), Heba